1991
DOI: 10.1099/00221287-137-7-1729
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and characteristics of endoglucanase gene engB from Clostridium cellulovorans

Abstract: An endoglucanase gene, engB, from ClostridYum cellulovorans, previously cloned into pUCl9, has been further characterized and its product investigated. The enzyme, EngB, encoded by the gene was secreted into the periplasmic space of Escherichiu coli. The enzyme was active against carboxymethylcellulose, xylan and lichenan but not Avicel (crystalline cellulose). The sequenced gene showed an open reading frame of 1323 base pairs and coded for a protein with a molecular mass of 48.6 kDa. The mRNA contained a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 24 publications
4
48
0
1
Order By: Relevance
“…They were very similar except that EngD had about four-times-greaterp-nitrophenyl 1-1,4-cellobiosidase activity, indicating the presence of cellobiosidase activity as originally reported (14). The purified enzymes retained the substrate specificities of the original clones (6,13,14). The specific activity of EngD was about 80 times greater than that of the unpurified periplasmic fraction of the E. coli clone, and the specific activity of EngB2 purified protein was about 70 times greater than that of the periplasmic fraction of the pC2-engB E. coli clone (6).…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations
“…They were very similar except that EngD had about four-times-greaterp-nitrophenyl 1-1,4-cellobiosidase activity, indicating the presence of cellobiosidase activity as originally reported (14). The purified enzymes retained the substrate specificities of the original clones (6,13,14). The specific activity of EngD was about 80 times greater than that of the unpurified periplasmic fraction of the E. coli clone, and the specific activity of EngB2 purified protein was about 70 times greater than that of the periplasmic fraction of the pC2-engB E. coli clone (6).…”
Section: Resultssupporting
confidence: 53%
“…The purified enzymes retained the substrate specificities of the original clones (6,13,14). The specific activity of EngD was about 80 times greater than that of the unpurified periplasmic fraction of the E. coli clone, and the specific activity of EngB2 purified protein was about 70 times greater than that of the periplasmic fraction of the pC2-engB E. coli clone (6). Isoelectric focusing showed that the isoelectric point of EngD was around 8.8 and that of EngB2 was 7.0 (data not shown).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Notably, several members of subfamily A4 have previously been reported to act on more than one substrate. For instance, GH5 proteins from Prevotella ruminicola (AAC36862.1) and Clostridium cellulovorans (AAA23231.1) have been reported to act on glucan as well as xylan substrates, although detailed biochemical characterization or structural information for these enzymes is not available (30,31). The most thoroughly characterized GH5 enzyme from subfamily A4 is the thermostable enzyme, Cel5A_Tma (AAD36816.1), from Thermotoga maritima (32).…”
Section: Building a High Quality Phylogenetic Tree For Gh5-thementioning
confidence: 99%